Bone formation by human umbilical cord perivascular cells. Issue 8 (11th February 2015) - Kajiyama, Sohtaro; Ujiie, Yuko; Nishikawa, Sumio; Inoue, Kohji; Shirakawa, Satoshi; Hanada, Nobuhiro; Liddell, Robert; Davies, John E.; Gomi, Kasuhiro
Abstract We investigated the possibility of employing human umbilical perivascular cells (HUCPVCs) within the context of finding an alternative source of mesenchymal stromal cells (MSC) for bone tissue engineering. Since it has previously been reported that conditioned medium (CM) from osteogenic bone marrow (BM) MSCs can potentiate osteogenic differentiation in a secondary cell population, we also employed BM‐MSCs to generate CM to stimulate osteogenesis in the HUCPVCs. The BM‐MSCs were a commercially available immortalized human cell line. In vitro assays showed negligible levels of osteogenic gene expression in HUCPVCs compared to BM‐MSC, but alkaline phosphatase was detected when HUCPVC were cultured in osteogenic medium in the presence of CM from BM‐MSC. An in vivo assay employing a rat calvarial osteotomy defect, together with a collagen sponge scaffold, showed that HUCPVCs provided statistically significant bony repair compared to controls. BM‐MSC loaded scaffolds were not statistically different from either controls or HUCPVCs. The addition of BM‐MSC CM to HUCPVCs also produced no statistically significant difference to the bone formed by HUCPVCs alone. Our results demonstrate that the in vitro assays employed did not predict in vivo outcomes, and that the BM‐MSC cell line employed, or CM from such cells, provided no osteogenic advantage over the use of HUCPVCs alone. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2807–2814, 2015.